2021
DOI: 10.18201/ijisae.2021473645
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evaluation and Prediction of Financial Time Series Using Hybrid Regression Prediction Models

Abstract: Financial time series are chaotic by nature, which makes prediction difficult and complicated. This research employs the new hybrid model for the prediction of FTS which comprises Long Short-Term Memory (LSTM), Polynomial Regression (PR), and Chaos Theory. First of all, FTS is tested for the presence of chaos, in this hybrid model. Later, using Chaos Theory, the time series is modelled with the chaos existence. The model time series will be entered in LSTM for initial forecasts. The sequence of errors derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Reference [21] discusses the difficulties of forecasting stock performance and the superiority of the suggested ensemble ARIMA-LSTM technique. In [22], a hybrid approach for predicting financial time series was presented. LSTM, Polynomial Regression (PR), and Chaos Theory make up the model.…”
Section: Related Workmentioning
confidence: 99%
“…Reference [21] discusses the difficulties of forecasting stock performance and the superiority of the suggested ensemble ARIMA-LSTM technique. In [22], a hybrid approach for predicting financial time series was presented. LSTM, Polynomial Regression (PR), and Chaos Theory make up the model.…”
Section: Related Workmentioning
confidence: 99%
“…One of the advantages of this method over linear regression is its capability to incorporate more intricate, curved relationships that closely resemble real-world phenomena. Durairaj and BH have employed polynomial regression models for the purpose of examining and predicting various financial data, including stock prices [6]. These models have demonstrated significant predictive abilities, surpassing linear models in terms of accuracy.…”
Section: Application Of Polynomial Regressionmentioning
confidence: 99%
“…This work includes recent attention in markets to sentiment analysis or event extraction. In Durairaj and Mohan (2019), a review of deep learning hybrids for financial time-series prediction can be found. According to the authors' definition, a hybrid forecasting model combines two or more stand-alone forecasting models into a combined model in the hope to improve prediction accuracy and overcome the deficiencies of stand-alone models.…”
Section: Price Forecastingmentioning
confidence: 99%